Production of the human-beta-defensin using Saccharomyces cerevisiae as a host - Čipáková, Ingrid; Hostinová, Eva (Protein peptide letters, 2005)
Studies of the human defensins have been hampered by the lack of a simple expression system allowing for rapid production of functional peptide forms. Here, we describe a Saccharomyces cerevisiae AH22 expression system that meets that condition. The 42 amino acid form of human beta-defensin-1 was expressed under the control of the ADH1 promoter. The optimum conditions for expression were determined and the stable maintenance of the pVT103L-hBD-1 chimeric vector in the yeast population was confirmed. Expressed hBD-1 was secreted into the medium (approximately 55 microg l(-1)) and purified using cation-exchange chromatography. Isolated defensin exhibited strong bactericidal effect on Escherichia coli ML-35p. We conclude that the expression system described here will be a useful tool where readily prepared and active forms of the human defensins are needed.
Keywords: Saccharomyces cerevisiae; Humans; proliferace buněk; Cell Proliferation; beta-defensiny; genetické vektory; rekombinantní proteiny; molekulární sekvence - údaje; lidé; Molecular Sequence Data; Recombinant Proteins; antibakteriální látky; Anti-Bacterial Agents; Genetic Vectors; Escherichia coli; beta-Defensins; Amino Acid Sequence; sekvence aminokyselin